¿Hacia una renovación de la Historia? Post-apocalipsis, ideología y lengua en Mecanoscrito del segundo origen de Manuel de Pedrolo - Gregori, Alfons (Studia Romanica Posnaniensia, 2020)
The aim of the present paper is to determine several fissures and inconsistencies leading to unsolvable ambiguities of meaning in Manuel de Pedrolo’s novel Typescript of the second origin by means of a critical analysing of its linguistic and ideological issues, specially its religious groundwork – which is both stylistic and related to ideological content. However, some elements weaken the narrative’s disrupting character, making almost inevitably the failure of this revolution, as it is evidenced in the epilogue. In short, Predolo’s novel may be interpreted as a strong claim against History.